The legal nature of the tax doctrine - Fedorchuk, Maryna (European Journal of Law and Public Administration, 2019)
Tax changes in the state are impossible without the influence of such a phenomenon as tax-legal doctrine. This concept is mentioned in numerous national scientific works, but a special study of this phenomenon is absent in the science of tax law of Ukraine. Therefore, the article is devoted to the study of the tax-legal doctrine of Ukraine. The article provides a comprehensive analysis of scientific concepts of legal doctrine and tax-legal doctrine in particular. The author analyzes the impact of tax-legal doctrine on tax practice. The article deals with judicial tax doctrines, which is another factor that can help protect the rights of taxpayers. Considerable attention is paid to the nature of the tax-legal doctrine of Ukraine. Anthroposocialcultural nature of the doctrine of tax law is explored in the article. In addition, an analysis of the dominance in the tax legal doctrine of Ukraine of the etatists principles of the tax law was conducted.
Keywords: Legal doctrine; tax-legal doctrine; etatist approach; anthroposocialcultural approach.